Comparison of 0.25% Levobupivacaine, 0.25% Bupivacaine, and 0.125% Bupivacaine for Duration and Magnitude of Action in Peripheral Arterial Blood Flow Induced by Sympathetic Block in Dogs. Issue 2 (1st March 2007) - Iwasaki, Tadaomi; Takahashi, Yoshiyuki; Kimura, Yoshiyuki; Yamazaki, Hajime; Yamaguchi, Shigeki; Kitajima, Toshimitsu
Abstract : Background and Objectives: The aim of this study is to compare 0.25% levobupivacaine with 0.25% bupivacaine and 0.125% bupivacaine to examine the duration and magnitude of vasodilative effect induced by sympathetic block. Methods: We measured mean arterial pressure (MAP), heart rate (HR), and right and left brachial-artery blood flow (BABF) before and after cervicothoracic sympathetic block in 24 dogs. The experimental protocol was designed as follows: (1) left cervicothoracic sympathetic block with 1.0 mL of 0.25% levobupivacaine (n = 8), (2) left cervicothoracic sympathetic block with 1.0 mL of 0.25% bupivacaine (n = 8), and (3) left cervicothoracic sympathetic block with 1.0 mL of 0.125% bupivacaine (n = 8). Results: MAP and HR did not change significantly throughout the study in either group. Left cervicothoracic sympathetic block with 0.25% levobupivacaine increased left BABF significantly from 5 minutes through 80 minutes after the block (baseline, 100%; peak at 10 minutes after the block, 185 ± 35%; P <.01). Left cervicothoracic sympathetic block with 0.25% bupivacaine increased left BABF significantly from 5 minutes through 100 minutes after the block (baseline, 100%; peak at 10 minutes after the block, 251 ± 47%; P < .01). Left cervicothoracic sympathetic block with 0.125% bupivacaine increased left BABF significantly from 5 minutes through 80 minutes after the block (baseline, 100%; peak at 10 minutes after the block, 155 ± 20%; P < .01). Conclusions: 0.25% Levobupivacaine may have a lower potency compared with 0.25% bupivacaine in sympathetic block in dogs.